Perspectives on Smoking among Female Smokers: A Qualitative Study from Kathmandu, Nepal - Oli, Sumina; Bhandari, Dikshika; Aryal, Usha; Sharma Upreti, Anish; Kackchapati, Sampurna (Health Prospect, 2022)
Introduction: Tobacco is one of the biggest public health threats the world has ever faced, killing nearly eight million people a year. The problem of smoking among females has not been well addressed in Nepal. The study aims is to identify reasons behind smoking initiation and maintenance from the perspective of female smokers in Nepal. Methods: A qualitative study was conducted among female smokers aged between 18-24 years using focus group discussion and individual interviews in different hotspots for smoking in Kathmandu valley, Nepal. The purposive sampling technique was used. The female smokers who had smoked at least once in the previous seven days and continuously for the previous six months were included in the study. The interviews and discussions were recorded and transcribed before thematic analysis was conducted. Results: Four major themes emerged from analysis -initiation of smoking, smoking behavior, reasons for smoking and beliefs about smoking. All the female smokers started smoking as teenagers, generally out of curiosity and influence from family members. They preferred to smoke in groups and some were forced to smoke by their friends and had smoked against their will until smoking became a habit. Other factors for them to smoke were stress, conflict, peer pressure, fashion and education factors. The participants regarded the sense of release and independence gained from smoking as important and perceived the health risks as slight. Conclusion: The different perspectives on smoking identified in this study suggest that public health interventions should aim to decrease smoking levels by targeting groups rather than individuals, focusing on changing the smoking behavior of families and strengthening the non-smoking policy in public places.